The privilege of man : a theme in Judaism, Islam and Christianity - Cragg, Kenneth, 1913-2012 (Religious studies : Bloomsbury Academic collections., 2016)
"This book is based on the 1967 Jordan Lectures in Comparative Religion and discusses the Biblical concept of human dominion and the Qur'anic doctrine of Adam as caliph. It explores the Jewish, Muslim and Christian understanding of man in election, the prophet-state and in grace and sonship."--Bloomsbury Publishing